Studies on the survival and growth of fry of Catla catla (Hamilton, 1922) using live feed - Kadhar, Abdul; Kumar, Arun; Ali, Jawahar; John, Akbar (Hindawi Publishing Corporation, 2014)
Effect of live feed on the survival and growth of fry of Catla catla using three different live feeds namely, Cyclopoid (Thermocyclops decipiens), Cladoceran (Moina micrura), and mixed diet (Cyclopoid and Cladoceran) were studied. Commercial feed (Sunder’s feed) was used as control. Feeding experiments were carried out in 100 L tanks for 40 days. Fish fry fed with the mixed diet showed significantly better survival rate (54.80 ± 2.43%) than those fed with other food types . Fish fry fed with Cyclopoid had significantly better growth (26.03 ± 1.88 mm, weight 61.07 ± 3.53 mg) than those fed with other food types. Biochemical studies showed higher level of protein, carbohydrate, and lipid content in Catla fry fed with Cyclopoid diet. The results are discussed in the light of the literature available. It could be suggested that the Cyclopoid diet can be used as live feed for effective production of Catla fry.